1992
DOI: 10.1088/0954-3899/18/1/013
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: In their theory of a y angular correlations, Rose and Brink leave the relative sign of different partial wave5 in a-capture undetermined. Some confusion has arisen in the experimental literature where the sign has also been considered as somewhat arbitrary for a-decay. We derive an explicit relation between these two processes and show how the above sign may easily be fixed by considering the simpler problem of a-decay of a deformed nucleus polarized in a strong magnetic field. We discuss the anisotropy of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 19 publications
0
38
0
Order By: Relevance
“…In this process dissipation (intrinsic excitations during transfer) and the evo lution of deformation must be avoided because the expense in energy will reduce the tunnelling probability. Numerous studies of coupled channel phe nomena in fusion reactions, related to inelastic excitations and transfer pro cesses [7,[66][67][68][69]76,77], have shown that the tunnelling process is embedded in a complicated multidimensional rearrangement process.…”
Section: Connections Between Transfer and Fusion Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…In this process dissipation (intrinsic excitations during transfer) and the evo lution of deformation must be avoided because the expense in energy will reduce the tunnelling probability. Numerous studies of coupled channel phe nomena in fusion reactions, related to inelastic excitations and transfer pro cesses [7,[66][67][68][69]76,77], have shown that the tunnelling process is embedded in a complicated multidimensional rearrangement process.…”
Section: Connections Between Transfer and Fusion Processesmentioning
confidence: 99%
“…Finally the question of channel coupling must be addressed, which has been mainly studied for lighter systems [66][67][68][69]76,77]. Only a short hint is given here.…”
Section: Fusions With Neutron Rich Projectiles and Other Future Prospmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, a number of theoretical calculations were performed to predict absolute α decay width, to extract nuclear structure information, and to pursue a microscopic understanding of α-decay phenomenon. These studies are based on various theoretical models such as the shell model, fissionlike model, and cluster model [18][19][20][21][22][23][24][25][26][27][28][29]. Recently, we studied favored α-decay half-lives for * Electronic address: zren@nju.edu.cn two different mass regions with the spherical version of the density-dependent cluster model (DDCM) [30].…”
Section: Introductionmentioning
confidence: 99%
“…[15]). Recently phenomenological evidence has been found [16] for an even more striking uniformity in even-even actinide nuclei. Experimental branching ratios of -transitions to different final states were used in a coupled-channel barrierpenetration model of the -decay of these deformed nuclei.…”
mentioning
confidence: 99%